Valorization of rambutan (Nephelium lappaceum) by-products: Food and non-food perspectives - Mahmood K. (2023)
Tropical fruits are of great significance in human diet due to abundant nutritional and antioxidants components. The processing or consumption of these fruits generates waste,which is generally disposed of into the ecosystem. However, efforts are in line to evaluate the nutritional worth and possible reuse of fruit processing waste by valorizing the waste in an optimal way. In this review, by-products of rambutan fruit waste, i.e., seed and peel, are signified with respect to their nutritional values and possible applications. Peel and seed cumulatively share almost around 50% of whole rambutan fruit by weight. Peel that is rich in phenolics and ellagitannins have applications as a natural antioxidant system. However, abundant fat content (14−41%) with high oleic acid, renders the seed a novel source of vegetable fat. Besides, possibilities of using seed fat in chocolate (30 wt.% substitute) and personal care products are also one of the focus. Nanostructured seed fat is reported for encapsulation off at-soluble vitamins (e.g., vitamin E). Additionally, the seed contains the most of the essential and non-essential amino acids that are concentrated as protein concentrate. The physico-functional properties of defatted seed flour and seed mucilage are also elaborated. Similarly, rambutan seed oil and peel utility as filler in packaging, bio-coagulant, bio-sorbent and alternative biodiesel are also mentioned. Despite diverse applications, gaps are still there to further evaluate and validate the potential of rambutan processing by-products. Thus, to avail the manifold potential, fruit by-products’ applications should be scaled up to transform the maximum waste into best.